Impact of demographic, genetic, and bioimpedance factors on gestational weight gain and birth weight in a Romanian population: A cross-sectional study in mothers and their newborns. Issue 27 (July 2016) - Mărginean, Claudiu; Mărginean, Cristina Oana; Bănescu, Claudia; Meliţ, Lorena; Tripon, Florin; Iancu, Mihaela
Abstract : Abstract: The present study had 2 objectives, first, to investigate possible relationships between increased gestational weight gain and demographic, clinical, paraclinical, genetic, and bioimpedance (BIA) characteristics of Romanian mothers, and second, to identify the influence of predictors (maternal and newborns characteristics) on our outcome birth weight (BW). We performed a cross-sectional study on 309 mothers and 309 newborns from Romania, divided into 2 groups: Group I—141 mothers with high gestational weight gain (GWG) and Group II—168 mothers with normal GWG, that is, control group. The groups were evaluated regarding demographic, anthropometric (body mass index [BMI], middle upper arm circumference, tricipital skinfold thickness, weight, height [H]), clinical, paraclinical, genetic (interleukin 6 [IL-6]: IL-6 -174G>C and IL-6 -572C>G gene polymorphisms), and BIA parameters. We noticed that fat mass (FM), muscle mass (MM), bone mass (BM), total body water (TBW), basal metabolism rate (BMR) and metabolic age ( P < 0.001), anthropometric parameters (middle upper arm circumference, tricipital skinfold thickness; P < 0.001/ P = 0.001) and hypertension (odds ratio = 4.65, 95% confidence interval: 1.27–17.03) were higher in mothers with high GWG. BW was positively correlated with mothers' FM ( P < 0.001), TBW ( P = 0.001), BMR ( P = 0.02), while smoking was negatively correlated with BW ( P = 0.04). Variant genotype (GG+GC) of the IL-6 -572C>G polymorphism was higher in the control group ( P = 0.042). We observed that high GWG may be an important predictor factor for the afterward BW, being positively correlated with FM, TBW, BMR, metabolic age of the mothers, and negatively with the mother's smoking status. Variant genotype (GG+GC) of the IL-6 -572C>G gene polymorphism is a protector factor against obesity in mothers. All the variables considered explained 14.50% of the outcome variance.